Highly Variable Sialylation Status of Donor-Specific Antibodies Does Not Impact Humoral Rejection Outcomes - Barba, Thomas; Harb, Jean; Ducreux, Stéphanie; Koenig, Alice; Mathias, Virginie; Rabeyrin, Maud; Pouliquen, Eric; Sicard, Antoine; Chartoire, Dimitri; Dugast, Emilie; Defrance, Thierry; Morelon, Emmanuel; et al. (Frontiers in Immunology, 2019)
Clinical outcome in antibody-mediated rejection shows high inter-individual heterogeneity. Sialylation status of the Fc fragment of IgGs is variable, which could modulate their ability to bind to C1q and/or Fc receptors. In this translational study we evaluated whether DSA sialylation influence antibody-mediated rejection (AMR) outcomes. Among 938 kidney transplant recipients for whom a graft biopsy was performed between 2004 and 2012 at Lyon University Hospitals, 69 fulfilled the diagnosis criteria for AMR and were enrolled. Sera banked at the time of the biopsy were screened for the presence of DSA by Luminex. The sialylation status of total IgG and DSA was quantified using Sambucus nigra agglutinin-based chromatography. All patients had similar levels of sialylation of serum IgGs (2%). In contrast, the proportion of sialylated DSA were highly variable (median=9%; range=0-100%), allowing to distribute the patients in two groups: high DSA sialylation (n=44; 64%) and low DSA sialylation (n=25; 36%). The two groups differed neither on the intensity of rejection lesions (C4d, ptc and g; p>0.05) nor on graft survival rates (Log rank test, p=0.99). In vitro models confirmed the lack of impact of Fc sialylation on the ability of a monoclonal antibody to trigger classical complement cascade and activate NK cells. We conclude that DSA sialylation status is highly variable but has not impact on DSA pathogenicity and AMR outcome.